The Mystery of Jesus' Teaching about “The Son of Man” - Beckstrom, Edward August (Biblical theology bulletin, 2012)
For centuries a mystery has surrounded the meaning of Jesus' term “The Son of Man” in his ministry, and today it is often called “The Son of Man Problem.” Studying “Son of Man” in all of its biblical references, and apocryphal usages, together with insights from the Dead Sea Scrolls, I propose a solution that the idiom means “Priest” or “High Priest,” but most especially “Heavenly High Priest” and is framed in the third person by Jesus because it is expressed as his destiny given by God—it is the Will of God. “The Son of Man” is distinct from Jesus own will, but is the destiny he follows. It is also the use of this term that caused Caiaphas to cry “blasphemy” at Jesus' Sanhedrin trial, who then sent him to Pilate for crucifixion, yet asserting that Jesus proclaimed himself “King of the Jews.” Caiaphas, knew, I believe, that “Son of Man” was synonymous with “High Priest.”